(untitled) (Medical Forum Monthly, 2022)
Objective: This research intends to identify whether or not patients with covid-19 may safely use psychiatric drugs. Study Design: Cohort study Place and Duration: This study was conducted at the Sahara Medical College Narowal from September, 2021 to March, 2022. Methods: Total 220 patients of both genders addicted to psychotropic medications were presented in this study. After obtaining informed written consent, detailed demographics of enrolled cases included age, sex, BMI, place of living and education status. PCR test was used to diagnose infectious disease. Patients were both symptomatic and asymptomatic. Patients were given antibiotics to cure from infectious disease. Outcomes were assessed in terms of safety and mortality among all cases. SPSS 24.0 was used to analyze all data. Results: We found that 140 (63.6%) cases were males and 80 (36.4%) cases were females. Mean age of the patients was 43.6±4.19 years and had mean BMI 26.8±6.35 years. Most common psychotic drug class was second generation followed by first generation, mood stabilizers, benzodiazepines and antidepressants among all cases. Co morbidities were respiratory disease, diabetes and hypertension among all cases. We found that, patients those used mood stabilizers had severity of disease and higher ICU stay as compared to the patients those used second generation antipsychotic class. We found higher numbers of mortality among patients of using mood stabilizers. Conclusion: In this research, we found that persons hospitalized for major mental illness who were prescribed second-generation antipsychotics had a lower chance of contracting COVID-19 than those who were prescribed valproic acid (a mood stabilizer).